(untitled) (Bangladesh Journal of Agricultural Research, 2010)
In a study at Joydebpur, the crop co-efficient values at initial, development, mid-season, and late season stages of hybrid maize (variety: BARI Hybrid Maize-I) were determined as 0.38, 0.87, 1.36, and 0.75, respectively. These locally determined values of BARI Hybrid Maize-I differed to some extent from those recommended by FAO. The corresponding FAO values are 0.4, 0.80, 1.15, and 0.70. The reasons might be that the FAO values are the generalized ones and recommended for a wide range of locations. But those determined by this study are location specific. Another reason may be the use of specific variety of hybrid maize in this experiment. However, locally determined values are preferred to standard values (FAO values) to estimate location specific crop ET. Keywords: Crop co-efficient; hybrid maize; lysimeter. DOI: 10.3329/bjar.v35i1.5868 Bangladesh J. Agril. Res. 35(1) : 77-82, March 2010